Library Automation : Change for Productivity in Service - Gopinath, M.A. (DESIDOC Journal of Library & Information Technology, 2002)
Library operations, in the context of the automation necessitate for an integrated approach and change in the perception of library's work. It examines the functional aspects, social aspects and system dynamics of library automation. Some strategies for library automation are suggested. http://dx.doi.org/10.14429/dbit.15.2.3180